Histamine exerts multiple effects on expression of genes associated with epidermal barrier function. - Gutowska-Owsiak, D; Salimi, M; Selvakumar, T; Wang, X; Taylor, S; Ogg, G (ESMON Publicidad S.A., 2014)
BACKGROUND: The role of epidermal barrier genes in the pathogenesis of atopic skin inflammation has recently been highlighted. Cytokines that are abundant in the skin during inflammation have been shown to exert various effects on the expression of barrier genes, although the role of histamine in this area of skin biology is not yet fully understood. OBJECTIVE: To assess the effect of stimulation with histamine on keratinocytes by analysis of the pathways involved in epidermal barrier integrity. MATERIAL AND METHODS: We performed a gene expression analysis of histamine-stimulated keratinocytes. Functional changes were tested using the dye penetration assay. Differential changes in filaggrin and the filaggrin-processing enzyme bleomycin hydrolase (BLMH) were validated at the protein level, and expression was also assessed in filaggrin knock-down keratinocytes. RESULTS: Histamine altered expression of multiple barrier genes. Expression of filaggrin was downregulated, as was that of other markers, thus suggesting the presence of delayed/aberrant keratinocyte differentiation. Expression of genes involved in cellular adhesiveness and genes of protease expression was dysregulated, but expression of protease inhibitors was increased. BLMH was upregulated in keratinocytes subjected to histamine and filaggrin knockdown. CONCLUSIONS: Histamine exerts a dual effect on epidermal barrier genes; it suppresses keratinocyte differentiation and dysregulates genes of cellular adhesiveness, although it induces genes contributing to stratum corneum function. Upregulation of BLMH and protease inhibitors could support maintenance of the permeability barrier by enhanced generation of moisturizing compounds and suppressed desquamation. In contrast, in the case of stratum corneum damage, histamine could enhance transcutaneous sensitization.